Je dois développer puis réduire :H= - 2 ( t - 3 ) ² - 5 ( 2 t - 5 ) ( - t + 3 )
J'ai fait :
H= [ - 2 ( t - 3 ) ² ] [ - 5 ( 2 t - 5 ) ( - t + 3 ) ]
H= ( - 2 t + 6 ) ² ( - 10 t + 25 ) ( - t + 3 )
H= ( 4 t ² + 24 t + 36 10 t ² - 30 t - 25 t + 75 )
H= 14 t ² - 31 t + 111
Mais je ne suis absolument pas sure !!!
Aidez moi svp :)))

1

Réponses

2014-10-26T17:46:18+01:00
H= - 2 ( t - 3 ) ² - 5 ( 2 t - 5 ) ( - t + 3 )
h = -2(t²-6t+9) -5(-2t²+6t+5t-15)
h = -2t²+12t-18 -5( -2t² +11t-15)
h =  -2t²+12t -18  +10t² -55t + 75
h =  8t² -43t-57